(Nie)obecność tematyki psychologicznej w ramach edukacji okołoporodowej w Polsce - Janowicz, Kamil (Człowiek i Społeczeństwo, 2024)
Antenatal education is becoming more popular and extended in recent years. For a long time, it was dominated by medical aspects – however, the frequency of the presence of psychological issues in antenatal education has increased in the last years. This paper presents the results of an analysis of the offer of antenatal education in 210 entities (public and private) from voivodeships cities in Poland regarding the presence of psychological themes in refund antenatal courses and extra classes. Data was gathered in Spring 2021 and analyzed by six trained coders (inter-coders agreement: Kendall’s-W = .72). Conducted analysis has revealed that psychological issues are rarely presented and discussed during the refund antenatal education course, on extra classes, and on the websites and social media fanpages of entities involved in organizing antenatal education. Additionally, only 16% of them offer the possibility of psychological consultations. These results show that antenatal education rarely addresses psychological issues like the psychological aspects of pregnancy, childbirth and the postpartum period, and childcare. While a transition to parenthood may be very challenging for both women and men, these findings suggest that antenatal education in Poland should be developed in terms of psychological issues. That should result in more complex support for new parents.